Numerical Well Testing Interpretation Method of Composite Model and Applications in Offshore Reservoirs by Polymer Flooding - Yu, Haiyang; Guo, Hui; Cheng, Shiqing; Li, Lei; Chang, Shuping; Zhang, Tiantian; Feng, Guozhi (Asian Journal of Chemistry, 2014)
This work presents numerical well testing method of composite model for formation evaluation by using pressure transient data, which are provided by CNOOC field tests. Since polymer flooding reservoirs are effected by multiple factors, the well testing composite models are established by considering wellbore storage effect, convection and diffusion. Typical curves, sensitivity analysis and history match are also conducted. In the Newtonian-non-Newtonian composite model, the pressure derivative curves of the transient section and the radial flow section obviously move upward with the increase of polymer viscosity. In the non-Newtonian-Newtonian composite reservoir, the greater of the oil viscosity, the greater magnitude upturned of the transition section. The data of polymer flooding field tests provided by CNOOC indicates that our work can accurately evaluate reservoir characteristics in relatively homogeneous offshore reservoirs by polymer flooding, which emphasizes the potential for the application of this method in relatively homogeneous offshore and onshore reservoirs.